Kesantunan Berbahasa Warganet dalam Menanggapi Usulan Gentengisasi pada Postingan Instagram Folkative - Asep Purwo Yudi Utomo; Esa Futuh Handa; Mohammad Sofwan Azizi; Syafa Rahmadani; Dariel Ramadhan Sahari; Ahc Fauzi; Cicha Kartikha Sri Mulyani; Alien Kurnia Warya Selia (Simpati, 2026)
This research arose from the growth of social media as an online public platform that influences communication methods, including netizens' politeness. The purpose of this study is to explain the types of illocutionary speech acts and analyze compliance and violations of politeness principles in netizens' responses to the proposed gentengization in Folkative's Instagram post. The method used was descriptive qualitative with a pragmatic approach. Data was collected through a listening and note-taking technique on the top 100–160 comments, then analyzed using the distribution method based on John Searle's speech act theory and Geoffrey Leech's politeness principles. The research findings indicate that netizens employed various speech acts, such as representative, directive, expressive, and commissive. In terms of politeness, compliance and violations were identified, with the most frequent violations occurring in the maxims of appreciation and agreement. This suggests that interactions on social media tend to be more expressive and less organized. This research contributes to enriching the study of digital pragmatics and raising public awareness of polite communication in online public spaces.